Management of fetal tumors. (July 2019) - Masmejan, Sophie; Baud, David; Ryan, Greg; Van Mieghem, Tim
Abstract: In this review article, we discuss the most common fetal tumors, their prenatal management, and outcomes. Overall, the most important outcome predictors are tumor histology, size, vascularity, and location. Very large lesions, lesions causing cardiac failure, and hydrops and lesions obstructing the fetal airway have the poorest outcome, as they may cause fetal death or complications at the time of delivery. Fetal therapy has been developed to improve outcomes for the most severe cases and can consist of transplacental therapy (sirolimus for rhabdomyomas or steroids for hemangiomas and microcystic lung lesions) or surgical intervention (shunting of cystic masses, tumor ablation, occlusion of blood flow or airway exploration, and protection). Given the rarity of fetal tumors, patients should be referred to expert centers where care can be optimized and individualized to allow the best possible outcomes. Highlights: Fetal tumors very often influence pregnancy management, location, and mode of delivery. Large and/or vascular lesions, especially those causing cardiac failure and hydrops, have the poorest outcomes. A multidisciplinary approach in an expert center is required to allow for the best outcomes.